RISK FACTORS INFLUENCING THE INCIDENCE OF PREDIABETES BASED ON SCREENING ACTIVITIES AT THE INTEGRATED NON-COMMUNICABLE DISEASES DEVELOPMENT POST (POSBINDU PTM) IN MEDAN KOTA DISTRICT HEALTH CENTER - Dita Purnama Sari Tarigan; Yulia Afrina Nasution (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2024)
The risk factors for prediabetes are the same as those for T2DM, such as a family history of Diabetes, female gender, obesity, and so on. Early detection of prediabetes can open the door for T2DM prevention interventions. This type of research is descriptive-analytic with a cross-sectional design. Data collection methods include medical records and field observation. Based on the results of the Spearman test, it was found that there was no significant relationship between gender (p-value=0.609, Correlation Coefficient=-0.079, opposite relationship), hereditary history of Diabetes (p-value=0.298, Correlation Coefficient=0.160, unidirectional relationship), and obesity (p-value=0.382, Correlation Coefficient=-0.135, opposite relationship) with the incidence of prediabetes based on screening at Posbindu PTM activities at Simpang Limun Health Center and Teladan Health Center. There is no significant relationship between gender, family history of Diabetes, and obesity with the incidence of prediabetes based on screening at Posbindu PTM activities at the Simpang Limun Health Center and Teladan Health Center.